Strategi Kebijakan Fiskal Terhadap Output dan Inflasi pada Perekonomian Indonesia dalam Menghadapi Dampak Virus Covid 19 - Ayu Feranika; Dini Haryati (Jurnal Inovasi Bisnis dan Kewirausahaan, 2020)
Abstract- This study aims to determine the fiscal policy strategy on output and inflation in the Indonesian economy in dealing with the effects of the covid virus 19. In this study, researchers chose to use descriptive research types, namely to explain an event whose operation revolves around data collection, data processing and data interpretation which is given a national meaning while still holding the principles of logic to form holistic conclusions. Data obtained through the study of literature, by reading and analyzing and analyzing a variety of literature, both in the form of documents, journals, publication data from the ministry of finance and from the official website that releases information that is relevant to research. While the data analysis is done by reducing, classifying, interpreting, and drawing conclusions. The Indonesian government adopted a comprehensive policy in the fiscal and monetary sector to deal with Covid-19. In the fiscal sector, the Government conducts a policy of refocusing activities and budget reallocation. From the revenue side, the government must pay attention to the contribution contribution from PPN and PPh Agency and from the expenditure side, the government must be able to pay attention to the realization of the use of these funds so that it is right on target and prioritizes the priority activities of the Covid pandemic prevention -19 To suppress the budget deficit. Abstrak– Penelitian ini bertujuan untuk mengetahui strategi kebijakan fiskal terhadap output dan inflasi pada perekonomian indonesia dalam mengahadapi dampak virus covid 19. Pada penelitian ini,peneliti memilih menggunakan tipe penelitian deskriptif, yaitu untuk menjelaskan suatu peristiwa yang operasionalisasinya berkisar pada pengumpulan data, pengolahan data dan penafsiran data yang diberi makna secararasional dengan tetap memegang prinsip-prinsip logika sehingga terbentuk kesimpulan yang holistik. Data diperoleh melalui studi literatur, dengan membaca dan menelaah serta menganalisa berbagai literatur, baik berupa dokumen, jurnal, data publikasi dari kementerian keuangan maupun dari website resmi yang mengeluarkan informasiinformasi yang relevan terhadap penelitian. Sementara analisa data dilakukan denganmelakukan reduksi, klasifikasi, pemaknaan hingga penarikan kesimpulan. Pemerintah Indonesia mengambil kebijakan yang komprehensif di bidang fiskal dan moneter untuk menghadapi Covid-19. Di bidang fiskal, Pemerintah melakukan kebijakan refocusing kegiatan dan realokasi anggaran.Dari sisi penerimaan, pemerintah harus memperhatikan pemberian kontribusi penerimaan dari PPN dan PPh Badan dan dari sisi pengeluaran, pemerintah harus mampumemperhatikan realisasi penggunaan dana tersebut agar tepat sasaran dan mengutamakan kegiatan prioritas pencegahan pandemik Covid-19 Untuk menekan defisit anggaran.